Direct Observation of the Triplet Metal‐Centered State in [Ru(bpy)3]2+ Using Time‐Resolved Infrared Spectroscopy. Issue 11 (22nd July 2016) - Mukuta, Tatsuhiko; Tanaka, Sei'ichi; Inagaki, Akiko; Koshihara, Shin‐ya; Onda , Ken
Abstract: [Ru(bpy)3 ] 2+ is well‐known as a prototype for the Ru(II) complexes used in a wide variety of photofunctional materials. The triplet metal‐centered ( 3 MC) state is important in this complex, since it dominates the phosphorescence lifetime and photoreaction processes. Despite this, the 3 MC state has not yet been observed by spectroscopic methods. In the present study, we demonstrated that time‐resolved infrared vibrational spectroscopy enables observations of the 3 MC state. A vibrational band at 1599 cm −1 was found to exhibit unique temporal behavior that differed from that of other bands assignable to the triplet metal‐to‐ligand charge‐transfer ( 3 MLCT) state. This unique behavior was assessed under various experimental conditions and it was concluded that the band arises from the short‐term population (∼23 ps) of the 3 MC state during relaxation to the bottom of the 3 MLCT state. These results agree with [Fe(bpy)3 ] 2+ spectra, which show that the 5 MC state is the most stable excited state. Abstract : Observation of an elusive state. The non‐luminescent triplet metal‐centered ( 3 MC) state in [Ru(bpy)3 ] 2+, which is a prototype for many Ru(II) polypyridyl complexes, dominates both the phosphorescence lifetime and photoreaction process but the state has not yet been observed by spectroscopic methods. Time‐resolved infrared spectroscopy makes it possible to observe the 3 MC state by careful examination of the temporal behavior of vibrational bands under various experimental conditions.